English as a Language of Learning at the University of Iceland. A Survey of Students' Perceived Proficiency - Tovazzi, Maddalena, 1988- (2011)
This essay reports the findings of a small survey conducted at the University of Iceland. Aims of the study were to investigate how well students think they are prepare to meet the English language requirement of the University curriculum. Not many studies have been focusing on the situations where the language of assestment is another one than the language of the textbooks. Students are also asked what they believe has been helpful in their learning of English. Although the study was a small one, some interesting aspects emerged which suggest further research on the issues presented would be useful. Scholarly positions are also briefly presented.